Perbedaan Frekuensi Pemberian Enteral Feeding terhadap Toleransi Feeding dan Kadar Glukosa Darah - Dewi Siti Oktavianti; Yulia Yulia; Riri Maria (Poltekkes Kemenkes Bengkulu, 2021)
Medical nutrition therapy is one of the interventions to provide sufficiently nutrition and to optimize glycemic controls in meeting the body metabolic needs. An Enteral Feeding is an alternative feeding method when there are obstacles to fulfill patients nutrition orally. This study aims to determine feeding tolerances and blood glucose controls in Type2 Diabetes Mellitus patients with different Enteral Feeding frequencies-three and six times preserving. This research is a quasi-experimental design study involving 26 patients admitted in a hospital. The results of the study on respondents with enteral feeding of a frequency 3x/24 hours found that 2respondents (15.4%) were tolerant with enteral feeding given and as many as 3respondents (23.1%) had normal blood glucose, while the results of the study for respondents with enteral feeding of a frequency 6x / 24 hours, 12 respondents (92.3%) were tolerant with enteral feeding given and as many as 12 respondents (92.3%) had normal blood glucose. The results showed that there was a statistically difference between the three times and six times Enteral Feeding with feeding tolerance (p = 0.005). There was a difference between the frequency of enteral feeding six times and three times in the blood glucose level (p = 0.005). Results of this study will assist in controlling blood glucose by regulating the timing of feeding in patients with type 2 diabetes mellitus.